Pelaksanaan Penilaian Hasil Pembelajaran Pendidikan Jasmani pada Siswa Tuna Grahita SLB Se-Kota Semarang - Harinda Fahmi; Andry Akhiruyanto (Universitas Negeri Semarang, 2023)
The purpose of this study was to determine the implementation of the assessment of physical education learning outcomes from the cognitive, affective, and psychomotor aspects of mentally retarded students in SLB Semarang City.This study uses a qualitative research method with a descriptive approach. Data collection techniques are carried out by observation, interviews, and documentation. The validity of the data is done by triangulation. Data analysis was carried out by collecting data, reducing data, presenting data, and drawing conclusions. The results showed that the implementation of the assessment of physical education learning outcomes from the cognitive aspect is given based on the knowledge ability of each student. Assessment of the affective aspect is given based on the ability and character of each student. Assessment of the psychomotor aspect is given based on the ability of the skills of each student.